Determinants of postpartum uterine atony in urban South Ethiopia: a community-based unmatched nested case-control study - Belayneh Hamdela Jena; Gashaw Andargie Biks; Yigzaw Kebede Gete; Kassahun Alemu Gelaye (BMC, 2023)
Abstract Background Uterine atony is the most common cause of postpartum hemorrhage, which is the leading preventable cause of maternal morbidity and mortality. Despite several interventions uterine atony-related postpartum hemorrhage remains a global challenge. Identifying risk factors of uterine atony helps to reduce the risk of postpartum hemorrhage and subsequent maternal death. However, evidence about risk factors of uterine atony is limited in the study areas to suggest interventions. This study aimed to assess determinants of postpartum uterine atony in urban South Ethiopia. Methods A community-based unmatched nested case-control study was conducted from a cohort of 2548 pregnant women who were followed-up until delivery. All women with postpartum uterine atony (n = 93) were taken as cases. Women who were randomly selected from those without postpartum uterine atony (n = 372) were taken as controls. Using a case to control ratio of 1:4, the total sample size was 465. An unconditional logistic regression analysis was done using R version 4.2.2 software. In the binary unconditional logistic regression model variables that have shown association at p < 0.20 were recruited for multivariable model adjustment. In the multivariable unconditional logistic regression model, statistically significant association was declared using 95% CI and p < 0.05. Adjusted odds ratio (AOR) used to measure the strength of association. Attributable fraction (AF) and population attributable fraction (PAF) were used to interpret the public health impacts of the determinants of uterine atony. Results In this study, short inter-pregnancy interval < 24 months (AOR = 2.13, 95% CI: 1.26, 3.61), prolonged labor (AOR = 2.35, 95% CI: 1.15, 4.83), and multiple birth (AOR = 3.46, 95% CI: 1.25, 9.56) were determinants of postpartum uterine atony. The findings suggest that 38%, 14%, and 6% of uterine atony in the study population was attributed to short inter-pregnancy interval, prolonged labor, and multiple birth, respectively, which could be prevented if those factors did not exist in the study population. Conclusions Postpartum uterine atony was related to mostly modifiable conditions that could be improved by increasing the utilization of maternal health services such as modern contraceptive methods, antenatal care and skilled birth attendance in the community.